Explanatory factors of collective competencies in fashion design teams - Silva, Luiz Henrique da; Schmitt, Tatiani; Silva, Francielle Molon da; Ghedine, Tatiana; Tutida, Alessandra Yula (Contextus - Revista Contemporânea de Economia e Gestão, 2022)
This article aims to identify the explanatory factors of collective competencies in fashion design teams using a survey of 22 fashion designers from Santa Catarina. Exploratory factor data analysis and analysis of variance techniques were applied. The results showed four explanatory factors: collective spirit, interaction, cooperation, and relationship. Our findings made evident how relevant these factors are in the composition and formation of groups, manifesting themselves as descriptive and essential attributes for collective competencies. The synergistic combination of the factors allows the teams to develop shared actions in favor of work organization based on interactions and visions, which, although distinct, can be shared.